ANALISIS YURIDIS TERHADAP HIBAH ANAK ANGKAT YANG DIBATALKAN (STUDI PUTUSAN NO.41/PK/AG/2009) - Ravienda Purnama; Hayatul Ismi; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
According to Islamic Law adopted children are not recognized as a basis for inheritance, because the main principle in inheritance is blood relations. One of the ways adopted children get inheritance is by way of grants. In the matter that the author discussed, the grant was given but was canceled by the wife of the donor. In decision No. 41 / PK / AG / 2009 The Panel of Judges rejected the request for a review of the defendant. The Panel of Judges in the previous ruling argued that the grant was a joint property of the Plaintiff Hj. Umi Kalsum and the late Drs. Adenan P. Ardjem. Article 212 KHI states that grants cannot be withdrawn except parents' grants to their children. The problems discussed in this thesis (1) How is the arrangement of grants to adopted children canceled and (2) How is the judicial analysis of the judge's decision on case No. 41 / PK / AG / 2009.In this study using a normative juridical approach. In this study the authors use library research techniques (Library Research) which is supported by secondary data based on its strengths are divided into three legal materials, namely primary legal material, secondary law, and tertiary legal materials.From the results of the research on the decision of case No.41 / PK / AG / 2009, the grant given to adopted children is an ordinary grant and the grant cannot be canceled if it has fulfilled the terms and conditions of the grant. Judges' consideration of the case does not fulfill the principle of legal certainty and justice for the plaintiff. The judges did not consider the evidence presented by the Defendant.